Bangsa Melayu Malay concepts of democracy and community 1945 - 1950 - Omar, Ariffin (South-East Asian historical monographs, 1993)
Bangsa Melayu is a study of political ideology in two related but distinct Malay communities in Peninsular Malaya and East Sumatra at a time of political ferment in the years immediately after the Second World War. Prior to this period, the kerajaan, or monarchy headed by the sultans, had been central to the Malay political culture and identity, but with the rise of nationalism, nation-states, and nationality in the Malay Archipelago, new alternatives were available to the Malays